Barriers to Physical Activity on University Student. (March 2017) - Jajat,; Sultoni, K; Suherman, A
Abstract: The purpose of the research is to analyze the factors that become barriers to physical activity in university students based on physical activity level. An internet-based survey was conducted. The participants were 158 University students from Universitas Pendidikan Indonesia. Barriers to Physical Activity Quiz (BPAQ) were used to assessed the factors that become barriers to physical activity in university students. IPAQ (short form) were used to assessed physical activity level. The results show there was no differences BPAQ based on IPAQ level. But when analyzed further based on seven factors barriers there are differences in factors "social influence and lack of willpower" based IPAQ level. Based on this it was concluded that the "influence from other and lack of willpower" an inhibiting factor on students to perform physical activity.